Measurement of Shariah compliant companies performance using Risk-Adjusted Methods: evidence from health care sector / Maizatul Akmal Nisak Khairol Mizar ... [et al.] - Khairol Mizar, Maizatul Akmal Nisak; Roseli, Nur Syahirah; Ahmad, Nurul Asyikin; Mohd Amin, Farah Azaliney (UiTM Cawangan Negeri Sembilan, 2021)
In recent years, the Islamic tinance industry growing exponentially due to the demands from Muslim investors that required halal products and investments that are in line with the Shariah principle (Ahmad &, Ibrahim, 2020; Ahmed & Siddiqui, 2019). An investment that is made based on Shariah-compliant principles is an example of an ethical investment. The demand increases because Islam is the second-largest religion in the world with forty-six countries having a Muslim population (Abdullah & Ahmad, 2010). Specifically, Muslims need to follow the Islamic law that has been set by the Quran and Sunnah. The Health Care sector was established in the Kuala Lumpur Shariah lndex in 2018. The companies in the Health Care sector play a vitaI role in providing health care equipment and services such as producing gloves, sterilization and medication for medical purposes. Currently, this sector is one of the fastest-growing sectors since the entire world experiencing the outbreak of Covid-19 disease including Malaysia. All types of investments, including Shariah-compliant stocks involve risk. Rule of thumb stated that high risk-high returns, which means the greater risk is borne, the greater the generated returns (Suryani & Herianti, 2015). This sector will benefit Muslim investors as the return of each company is higher due to the demand of the current condition. By considering the situation, it has motivated this study to examine the overall performance of local Shariah-compliant companies, especially in the Health Care sector.